2004
DOI: 10.1007/s11159-004-2623-5
|View full text |Cite
|
Sign up to set email alerts
|

Privatisation Of Education In Canada: A Survey Of Trends

Abstract: The construct of 'neo-liberalism' well defines privatisation within a global convergence of educational policy discourses and practices. This study analyses initiatives for and processes of privatisation in Canadian education from K-12 to post-secondary levels. In considering how privatisation is affecting public education systems in Canada, the authors focus on the commodification and marketisation of education. They also examine issues of equity and the viability of universally accessible and publicly funded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…According to David Harvey (2007), the neoliberal policies that have been implemented across the Anglo-American world (and elsewhere) since the 1970s can be understood as part of a project to restore class power after the post-war class compromise had diminished the share of national wealth held by elites. Education has not been exempted from these policies; it has been directly impacted by deregulation, privatisation and marketisation which have allowed for the growth of private and charter schools, private partnerships, deregulated tuition, and additional fees (Davidson-Harden and Majhanovich 2004). Moreover, market proxies and logics have been used to manage the residual public education sector, and civil society actors such as NGOs and charities have been encouraged to pick up the slack caused by budget cuts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to David Harvey (2007), the neoliberal policies that have been implemented across the Anglo-American world (and elsewhere) since the 1970s can be understood as part of a project to restore class power after the post-war class compromise had diminished the share of national wealth held by elites. Education has not been exempted from these policies; it has been directly impacted by deregulation, privatisation and marketisation which have allowed for the growth of private and charter schools, private partnerships, deregulated tuition, and additional fees (Davidson-Harden and Majhanovich 2004). Moreover, market proxies and logics have been used to manage the residual public education sector, and civil society actors such as NGOs and charities have been encouraged to pick up the slack caused by budget cuts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More broadly, the very purpose of education has been shifted with increasing emphasis on producing human capitalstandard-tested, job-ready workers to meet market demands and enhance the competitiveness of the state and capital (Brown 2015). Although public school education in Canada has been less aggressively restructured than in the United States, the neoliberal context of budget cuts, the growth of private schools, the introduction of public-private partnerships and standardised tests, and the emphasis on job-readiness have significantly reshaped public education across Canada's provincial school systems (Davidson-Harden and Majhanovich 2004;Noonan and Coral 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This understanding of corporatization is the main concern of the research leading to this paper. The fact that there is much literature showing a concern with the push to the corporatization of education (Coates & Morrison, 2011;Côté & Allahar, 2011;Davidson-Harden & Majhanovich, 2004;Hacker & Dreifus, 2010;Häyrinen-Alestalo & Peltola, 2006;Newfield, 2008;Slaughter & Rhodes, 2009;Tuchman, 2011) implies that a change has occurred. But what has changed and why?…”
Section: The Corporatization Shiftmentioning
confidence: 99%
“…However, studies on the NAFTA's influence on the region have shown that policies of economic liberalization have indirectly impacted education. For example, Davidson-Harden & Majhanovich [24] indicated that free trade without tariff barriers brings more education service companies into the education business at various levels, leading to an increase in education privatization. Chiang [25] examined the changes in globalization of higher education and suggested that NAFTA, led by the US, had established professional diploma and certification standards 1)…”
Section: ) Formation Of Education Policiesmentioning
confidence: 99%